Skin infections in children in northern Abidjan - Ivory Coast. - Komenan, K.; Ange, A.; Kanga, K.; Alexandre, K.; Elidja, E.; Ildevert, G.; Abdoulaye, S. (European Journal of Pediatric Dermatology, 2019)
Skin infections represent a public health problem in sub-Saharan Africa, mainly in poor communities with defective environmental and socio-economic conditions. The infections are mainly caused by bacterial, fungal, parasitic or viral agents. Children who are careless of the hygienic state are mostly concerned. A retrospective and descriptive study of all cases of skin infections in children was conducted in order to appreciate their prevalence among them. We recorded 1902 cases of dermatoses out of 7920 children received in consultation from 1st January, 2013 to 31st December, 2017. The majority of children were females, with a sex-ratio of 0.68.The average age was 4.8+/-1.5 years. Bacterial infections were most frequently reported (67.51%). We found only 4.9% of viral infections. The five common skin infections observed in our series were folliculitis, impetigo, scabies, ectyma and dermatophytoses. Bacterial infections were common in preschool and school children. Parasitic dermatoses were mostly observed in infant and preschool children. On the other hand, fungal skin infections were common in adolescents. As skin infections were mainly favored by poor socio-economic status and low education level, we need to set up strategies for population awareness and health practitioner’s training.